No impact of story context and avatar power on performance in a stop-signal game - Linus Held; Johannes Pannermayr; Alina Kaufmann; Marouscha Scheffer; Paola Flores; Martin Dechant; Maximilian A. Friehs (Heliyon)
This study investigates the impact of gamification on response inhibition in a Stop-Signal Task (SST) and examines participants' gamification experience. The findings reveal that, after accounting for approach- and avoidance-motivation as well as impulsiveness, higher immersion is associated with impaired response inhibition. This effect could be attributed to a substantial decline in immersion between the first and second SST sessions. Despite intrinsic motivation and avatar identification not significantly predicting performance, both factors exhibited a decline across sessions, suggesting an overall diminished gaming experience in the second session. Alternatively, motivational variables as immersion and avatar identification might be detrimental to response inhibition, by shifting attention away from relevant task elements. Contrary to expectations, approach and avoidance narratives did not influence outcome variables or participant experience, while different avatars led to altered avatar identification, particularly favouring strong avatars. The declining motivation over time might stem from a lack of tangible goals within the gamified task, where narrative elements alone failed to induce sufficient goal-oriented motivation. These findings underscore the nuanced interplay between gamification elements, task complexity, and participants' expectations, emphasizing the need for carefully tailored gamification strategies in experimental designs.